2020
DOI: 10.1111/cod.13672
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric contact allergy: A comparative study with adults

Abstract: Background: Pediatric allergic contact dermatitis is increasing. The patch test allergens included in pediatric baseline series vary globally. The worldwide prevalence of pediatric reactions to allergens needs clarification. Objectives: Identify the prevalence, associated factors, and culprit allergens for contact allergy among patch-tested Thai children, and compare with those for adults. Methods: Baseline series patch test results from 2010-2019 were collected for patients younger than 18 years of age. As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
5
1
Order By: Relevance
“…12,17,19 The mean age of our patch tested children was 10.9, which is younger than reported in some other recent studies, that is, 13.3 and 14.5 years, respectively. 18,20 A female predominance (ratio almost 2:1) was noted in children with a positive patch test, which confirms the results of most previous studies. 12 Within our study population, about half of the children were known with pre-existing AD (54.4%), a significant figure in contrast to other recent European studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…12,17,19 The mean age of our patch tested children was 10.9, which is younger than reported in some other recent studies, that is, 13.3 and 14.5 years, respectively. 18,20 A female predominance (ratio almost 2:1) was noted in children with a positive patch test, which confirms the results of most previous studies. 12 Within our study population, about half of the children were known with pre-existing AD (54.4%), a significant figure in contrast to other recent European studies.…”
Section: Discussionsupporting
confidence: 88%
“…Other recent European studies show even higher rates in their selected patient population (46.7% and 46%, respectively 3,18 ), while the prevalence rates in North America are even significantly higher 12,17,19 . The mean age of our patch tested children was 10.9, which is younger than reported in some other recent studies, that is, 13.3 and 14.5 years, respectively 18,20 …”
Section: Discussioncontrasting
confidence: 43%
“…31 We observed a prevalence of fragrance allergy similar to that of recent studies, 2,4 even if in our study a higher sensitivity rate for fragrance mix-2 (3.2%) than fragrance mix-1 (2.1%) was documented. The greater role of new fragrances than old fragrances as contact sensitizers in children, also recently observed by others, 41 confirms the necessity to periodically re-evaluate the fragrance mix composition according to EU cosmetic legislation. 42 Moreover, the significant difference of positive patch test reactions to fragrance mix-1 between children with and without AD is controversial in literature, confirming the findings of previous studies 22,43 and differing from others.…”
Section: Discussionsupporting
confidence: 73%
“…linalool, respectively 37 . In general, contact sensitization is uncommon in children or young adults, and the prevalence rates of positive reactions were found to be lower in children for most of the allergens in the baseline series 38 . Early and prolonged exposure to allergens could be an explanation for diagnosing contact sensitization cases in the lower age groups of patients.…”
Section: Discussionmentioning
confidence: 95%
“…Surprisingly, we found that the patients who had exclu- 37 In general, contact sensitization is uncommon in children or young adults, and the prevalence rates of positive reactions were found to be lower in children for most of the allergens in the baseline series. 38 Early and prolonged exposure to allergens could be an explanation for diagnosing contact sensitization cases in the lower age groups of patients. Limonene and linalool were also found in nearly 30% of baby care products, 10 while other common allergens in fragrance mix I and II were rarely found.…”
Section: Clinical Characteristics Of Patients With Ox Terpenes Allergymentioning
confidence: 99%